2007
DOI: 10.2478/s11686-007-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi-triatomine associations and the presence of mixed infections in single triatomine bugs in Paraná state, Brazil

Abstract: Eighteen strains of Trypanosoma cruzi isolated from two species of triatomines in the state of Paraná, Brazil, were characterized molecularly using three strategies: RAPD (randomly amplified polymorphic DNA) with four primers, analysis of the D7 polymorphic region of the 24Sα rDNA, and RFLP (restriction fragment length polymorphism) of region 5' of the mitochondrial gene COII (cytochrome oxidase subunit 2). The phenogram constructed with the RAPD data showed that only three strains isolated from Panstrongylus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
(49 reference statements)
1
14
1
Order By: Relevance
“…This result confirms that of Spitzner et al (2007), who also analysed isolates from the present study, and observed the occurrence of mixed infections in 50% of specimens of T. sordida and P. megistus captured in northwestern Paraná. Additionally, the 24S␣ rRNA, COII haplotypes, and microsatellite analyses performed in A316A, the isolate studied here and by Spitzner et al (2007), derived single cells separated by FACS Cell Sorter and showed that this strain is composed by two subpopulations, one belonging to TcII and another belonging to TcI. Furthermore, these two subpopulations displayed distinct microsatellite profiles (unpublished results).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…This result confirms that of Spitzner et al (2007), who also analysed isolates from the present study, and observed the occurrence of mixed infections in 50% of specimens of T. sordida and P. megistus captured in northwestern Paraná. Additionally, the 24S␣ rRNA, COII haplotypes, and microsatellite analyses performed in A316A, the isolate studied here and by Spitzner et al (2007), derived single cells separated by FACS Cell Sorter and showed that this strain is composed by two subpopulations, one belonging to TcII and another belonging to TcI. Furthermore, these two subpopulations displayed distinct microsatellite profiles (unpublished results).…”
Section: Discussionsupporting
confidence: 95%
“…The results of this study, together with those of Spitzner et al (2007) and Zafra et al (2008), showed that it was necessary to analyse also the COII gene in order to identify mixed infections in triatomines in southern Brazil and in chronic chagasic patients in Colombia, respectively. On the other hand, limitations to rRNA analyses were observed in this study and in others (Steindel et al, 2008;Zafra et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The host may influence the parasite, affecting its metabolic versatility over the wide range of environmental conditions where the hosts live 50 . Also, another study found that half of the triatomines analyzed in Paraná were co-infected by parasites from both T. cruzi I and II lineages 43 .…”
Section: Discussionmentioning
confidence: 99%